1952
DOI: 10.1021/ed029p513
|View full text |Cite
|
Sign up to set email alerts
|

Radiocolloids

Abstract: Examines the properties, means of detection, and experimental applications of radiocolloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1953
1953
1975
1975

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…also more stable and during its centrifugation it is agglomerated to a lesser extent than in the case of trace concentrations. The decrease of the portion separable by the centrifugation with an increasing carrier concentration could also be attributed to forming adsorption radiocolloids [15,16]. The sorption capacity of colloidal impurities randomly present in the solution is relatively low and at higher carrier concentrations a larger portion of ionic forms of the radionuclide will remain non-adsorbed in the solution.-As mentioned above, the presence of this type of radiocolloid is of a less probability.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…also more stable and during its centrifugation it is agglomerated to a lesser extent than in the case of trace concentrations. The decrease of the portion separable by the centrifugation with an increasing carrier concentration could also be attributed to forming adsorption radiocolloids [15,16]. The sorption capacity of colloidal impurities randomly present in the solution is relatively low and at higher carrier concentrations a larger portion of ionic forms of the radionuclide will remain non-adsorbed in the solution.-As mentioned above, the presence of this type of radiocolloid is of a less probability.…”
Section: Resultsmentioning
confidence: 97%
“…The peptization of the colloidal 144 Ce(III) started from 10~3 M CaCl 2 at both pa, from 10" 2 M NaCl at pn 7.0 and from 10" 1 M NaCl at ρχ 9.0. Multivalent cations can in certain cases suppress the "adsorption colloid" formation, because of their competition in the adsorption process [14][15][16], This effect obviously did not occur since, by contrast, up to 10 -3 M CaCl 2 the portion separable by the centrifugation increased and its subsequent decrease can be more probably explained by the above-mentioned peptization action. Thus, particles consisting prevalently of 144 Ce(III)-hydroxide and not foreign particles with a sorbed radionuclide are separated in this case.…”
Section: Resultsmentioning
confidence: 99%
“…In order to do so one needs exact information on the surface area of the adsorbent. Several attempts to calculate surface coverages in the adsorption of hydrolyzed metal ions have been reported (4,10,11,24,27). None of these results can be accepted as meaningful because the geometric surface area was always used in the calculations which is certainly smaller than the true surface area of the adsorbent.…”
Section: Discussionmentioning
confidence: 99%
“…The term pseudo-colloid is used to describe the formation of a colloid system Downloaded by MICHIGAN by the adsorption of a radioelement on solid impurities contained in the solution (7,8,29). While the nature of "radiocolloids" is still contro versial (25,27) the meaning of "pseudo-colloids" is completely obscure.…”
mentioning
confidence: 99%
“…The chemical behavior of YO1 in pure solutions has been studied by Kurbatov and Kurbatov ( 1 ) and Schweitzer and Jackson (2 ) who found that at a pH above 3, a portion of the yttrium will no longer pass through filter paper and becomes partially removable by centrifugation. The yttrium-9 1 used was carrierfree and therefore present in a low enough concentration so as not to affect the system under study.…”
mentioning
confidence: 99%